O geossistema do Córrego do Couto, PETAR, Iporanga - SP: uma contribuição ao levantamento do patrimônio espeleológico - Martins, Carlos Eduardo (2014)
This text deals with the importance of a karst spring. The Cachoeira do Córrego do Couto is one of the attractions of the Parque Estadual e Turístico do Alto Ribeira - PETAR, Iporanga - SP. The site is a resurgence of existing karst aquifer in a range between depressed carbonate rock saws higher impervious surfaces. The aquifer is composed of autologous and allogeneic systems water recharge, characterized for this reason as a mixed karst. As the object of study is a component of a landscape that remains dynamic relationships with society and also presents aspects of natural and human history, it is believed that the best approach for implementation of this work is the concept of geosystem. The concept is quite geosystem employed in studies of objects that have a natural origin, but are influenced by human activities. The results of the surveys carried out are a zoning map of the karst. In this map, the features are at the same time, resulting from and interact in the morphogenetic process responsible for landscape planning in the context of PETAR aims to provide recreation visitors for their aesthetic attributes